1999
DOI: 10.1063/1.478471
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopic study of rovibrational states of perdeuterated methane (CD4) trapped in parahydrogen crystal

Abstract: Articles you may be interested inSurvey of the high resolution infrared spectrum of methane (12CH4 and 13CH4): Partial vibrational assignment extended towards 12 000 cm−1The triply degenerate stretching ( 3 ) and bending ( 4 ) modes of CD 4 in solid parahydrogen at cryogenic temperatures are studied by Fourier transform infrared spectroscopy to reveal crystal field split rovibrational structures. The observed spectra are analyzed by taking into account the crystal field potential which is constructed by the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 15 publications
(38 reference statements)
3
21
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The p-H 2 matrix is capable of providing not only high resolution spectroscopic information regarding embedded molecules but also subtle intermolecular interaction between trapped molecules and the matrix hydrogen molecule. 12,13,[15][16][17][18]21,22 The feasibility of the study of in-situ photolysis stems from the fact that molecules in solid p-H 2 happen to be free from the cage effect, which allows us to study photolytically produced fragments such as radicals originating from the parent molecule. 9,14,[23][24][25][26] In a previous paper we have observed Fourier transform infrared ͑FTIR͒ spectra of the CD 3 radical trapped in solid p-H 2 crystal.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The p-H 2 matrix is capable of providing not only high resolution spectroscopic information regarding embedded molecules but also subtle intermolecular interaction between trapped molecules and the matrix hydrogen molecule. 12,13,[15][16][17][18]21,22 The feasibility of the study of in-situ photolysis stems from the fact that molecules in solid p-H 2 happen to be free from the cage effect, which allows us to study photolytically produced fragments such as radicals originating from the parent molecule. 9,14,[23][24][25][26] In a previous paper we have observed Fourier transform infrared ͑FTIR͒ spectra of the CD 3 radical trapped in solid p-H 2 crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Although we have discussed the spectra obtained from rapid vapor deposited CH 4 In an attempt to directly observe the effects of increasing structural disorder on the spectroscopy of CH 4 /pH 2 solids, we performed a series of sample in vacuum depositions >2 El 1 | j -2,2-2) +12,2-2) +1-2,2,2) +12,2,2)], -)=|o,2,-2) + |0,2,2)],…”
Section: Other Possible Microscopic Structures For Vapor Depositedmentioning
confidence: 99%
“…8 " 10 Detailed analysis shows the existence of quantized CH 4 rotational states, with all spectral features consistent with trapping of CH 4 14 We define the crystal axis such that hydrogen molecules occupy the lattice points located at R, = /,a, + / 2 a 2 + / 3 a 3 where a, = a(i + j), In order to analyze the rovibrational states of methane interacting with parahydrogen, we need to consider the interaction which depends only on the orientation of methane. The interaction potential for a methane in an fee crystal has to be invariant under any symmetry operation of the extended group Gf cc .…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic is demonstrated by our observation of the highly resolved rotation-vibration spectra of CH 4 and CD 4 in the p-H 2 matrix. [17][18][19] In the CH 4 /p-H 2 system we found that the matrix-isolated CH 4 monomer exhibits fine spectral splittings which provide us with quantitative information on the subtle intermolecular interaction between the CH 4 molecule and the matrix. 20 Not only the isolated monomer but also clusters of CH 4 show a rather rich spectral structure 21 that indicates that the parahydrogen matrix is also useful for the study of molecular clusters.…”
Section: Introductionmentioning
confidence: 97%